Effects of terrestrial runoff on the coral communities in Santiago Bay, Colima, Mexican Pacific Coast - Liñán-Cabello, Marco Agustín; Olivos-Ortiz, Aramis; Quijano-Scheggia, Sonia; Muñiz Anguiano, Daniela; Reséndiz-Flores, María Luisa; Ortega-Ortiz, Christian D. (Revista de Biología Tropical, 2016)
Coral reef ecosystems are under stress of different origins, from factors including sedimentation, fragmentation, overfishing, and tourism, depending on their geographical location, depth, and proximity to recreation areas. In this study of Juluapan Lagoon, we examined the relationship between various water-quality attributes and the status indicators of the coral community at La Boquita reef. During 2011 (12 months of sampling), six monitoring stations in the Juluapan lagoon were established in order to observe the gradient of the distribution of the physicochemical parameters: three stations on the upper part, or BI, (S4 to S6) and three more in the lower part, or BII, (S1 to S3). A control station (CS) was located in the coral reef close to the lagoon channel, and where dissolved inorganic nutrients and cellular carbon content were determined. Additionally, we considered the monitoring of three of the eight largest coral structures/headlands of this community: the first was the station closest to the channel communicating with Juluapan lagoon (C1), the second was in the intermediate region with respect to that lagoon (C2), and the third was farthest from the channel (C3). Three line intercept transects (LIT) 30 m in length and perpendicular to the coast provenance were established in each station, and the parameters indicative of the status of corals were evaluated in an area of 60 m2 on each transect (180 m2 by the station). Turbidity, evidence of fishing, signs of settling, algal coverage, abundance of fish, rate of sediment, and coral health records (as for CoralWach chart) were determined in situ and from digital photographs and videos. Considering various community status indicators used in the reef area, we could recognize a state of general deterioration, which was reflected in the loss of 17 % of coral coverage. The main anthropogenic disturbances in adjacent areas to La Boquita reef included wastewater discharges into the lagoon, tourist developments in the coastal zone, deforestation and erosion resulting from inappropriate development, and the runoff of nutrients from agricultural lands nearby the lagoon. All these significantly contributed to the nutrient-enriched waters of the lagoon, especially in summer, with negative effects on the coral community. Continued exposure to these factors, coupled with the lack of control over other anthropogenic components, has promoted the maintenance of a chronic stress state in the studied coral community. Our findings highlight the need for the development of appropriate coastal management and conservation policies for the coral reefs of the Mexican Pacific Coast.